Preparation method of aggregate with wave-absorbing function, anti-radiation wave-absorbing concrete and preparation method of anti-radiation wave-absorbing concrete

By preparing the coordinated use of high-magnetic wave-absorbing functional aggregate and cement slurry, the problem of existing wave-absorbing concrete lacks protection against high-frequency electromagnetic waves, achieving multi-band absorption and protection of microwaves and X-rays/γ-rays, and improving the mechanical properties of concrete.

CN119874237APending Publication Date: 2025-04-25SHANGHAI CONSTR BUILDING MATERIALS TECH GRP CO LTD +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411980024.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing absorbent concrete lacks protection against X-rays and gamma rays with high frequency and strong penetration, and the aggregate lacks functionality, which hinders the functional pathways in cement slurry.

Method used

By preparing high-iron fly ash containing magnetite and hematite, high-magnetic and high-density wave-absorbing functional aggregates are prepared through baking, magnetic separation and inert atmosphere sintering, and used in conjunction with cement slurry, magnetite sand, steel fibers and graphene oxide materials to form radiation-proof wave-absorbing concrete.

Benefits of technology

It realizes efficient absorption of microwaves and protection of X-rays and gamma rays with high frequency, while ensuring the mechanical properties of concrete and the wideband of wave absorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005221326190000071
    Figure BDA0005221326190000071
Patent Text Reader

Abstract

The invention relates to a preparation method of aggregate with a wave-absorbing function, anti-radiation wave-absorbing concrete and a preparation method, hematite in high-iron fly ash is reduced into magnetite, then high-magnetism fly ash with high iron content is screened out through magnetic separation, and the high-magnetism fly ash is sintered into the aggregate with the wave-absorbing function and high magnetite content in an inert atmosphere; the obtained aggregate with the wave-absorbing function is used for the anti-radiation wave-absorbing concrete, and the anti-radiation wave-absorbing concrete is prepared from the following components in parts by mass: 250 to 350 parts of cement, 85 to 95 parts of low-magnetism fly ash, 55 to 65 parts of mineral powder, 800 to 850 parts of the aggregate with the wave-absorbing function, 1200 to 1400 parts of magnetite sand, 40 to 65 parts of steel fiber, 0.09 to 0.4 part of graphene oxide, 5 to 6 parts of a water reducing agent and 175 to 185 parts of water. The anti-radiation and wave-absorbing concrete is simple in raw materials, has good wave-absorbing performance and anti-radiation performance on the premise of not influencing mechanical properties, improves the wave-absorbing broadband of the concrete, and has protection capability on X-rays and gamma-rays with high frequency and high penetrability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building materials, and in particular to a method for preparing a wave-absorbing functional aggregate, radiation-proof wave-absorbing concrete and a preparation method thereof. Background Art

[0002] Conventional absorbing concrete is made by adding absorbing materials such as carbon fiber, carbon nanotubes, graphite, carbon black, and ferrite to cement paste. However, due to the limited volume proportion of cement paste in concrete, the role of the above-mentioned absorbing materials is very limited, and the aggregates that account for a large volume proportion in concrete still do not have the corresponding functions, and even block the passage of functional phases in the cement paste. Conventional radiation-proof concrete uses heavy aggregates such as barite and iron ore to increase the density of concrete, improve its Compton effect and photoelectric effect, and thus improve its performance in protecting against X-rays and gamma rays.

[0003] Prior art, such as patent document with publication number CN106278001A, discloses an electromagnetic wave concrete and a preparation method thereof, which uses absorbing functional aggregate as aggregate, and the absorbing functional aggregate and absorbing cement slurry jointly exert the electromagnetic wave absorbing function. However, the concrete prepared by this technology mainly has a good absorption effect for microwaves with longer wavelengths, but lacks protection against X-rays and gamma rays with higher frequencies and stronger penetration. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a method for preparing an absorbing functional aggregate, an anti-radiation absorbing concrete and a preparation method. Through the functional synergy of the absorbing functional aggregate and the cement paste, the prepared anti-radiation absorbing concrete has high microwave absorption efficiency, good absorbing effect, a wide absorbing band, and excellent radiation protection performance. It has the ability to protect against X-rays and gamma rays with higher frequency and stronger penetration, and can ensure the mechanical properties of the concrete.

[0005] The technical objectives of the present invention are achieved through the following technical solutions:

[0006] A method for preparing a wave-absorbing functional aggregate, comprising:

[0007] S1. placing high iron fly ash containing magnetite and hematite in a roasting furnace, and roasting at a roasting temperature of 800° C. for 30 min to obtain roasted fly ash A, wherein the roasted fly ash A contains magnetite;

[0008] S2, dispersing the calcined fly ash A in water to obtain a calcined fly ash solution B, separating the magnetic substance in the calcined fly ash solution B to obtain wet high magnetic fly ash C and low magnetic fly ash solution D;

[0009] S3, drying the wet high magnetic fly ash C to constant weight to obtain high magnetic fly ash; drying the low magnetic fly ash solution D to constant weight to obtain low magnetic fly ash;

[0010] S4, granulating the high magnetic fly ash to form raw aggregate balls E with wave absorbing function;

[0011] S5, calcining the wave absorbing functional aggregate green ball E in an inert atmosphere, including three stages:

[0012] In the first stage, the preheating temperature is 400°C and the preheating time is 30 minutes;

[0013] In the second stage, the calcination temperature was 1200°C and the sintering time was 20 min;

[0014] In the third stage, rapid cooling for 15 minutes, the temperature drops to room temperature, and a coarse wave-absorbing functional aggregate F is obtained;

[0015] S6. Screening the coarse wave-absorbing functional aggregate F to obtain wave-absorbing functional aggregate, the apparent density of which is 2300-2500 kg / m 3 , cylinder pressure strength is 10~12MPa, and particle size is 5~20mm.

[0016] Furthermore, the Fe2O3 content in the high iron fly ash is 14% to 20%, the SiO2 content is 45% to 54%, the Al2O3 content is 25% to 30%, the Na2O content is 0.5% to 1%, the K2O content is 0.5% to 1%, the CaO content is 1% to 4%, the MgO content is 0.5% to 3%, and the residual carbon content is 4% to 6%.

[0017] Furthermore, the mass ratio of the calcined fly ash A to water is 1:9 to 1:4.

[0018] Furthermore, the content of Fe2O3 in the high magnetic fly ash is 45% to 60%, and the content of Fe2O3 in the low magnetic fly ash is 2% to 6%.

[0019] The present invention also provides a radiation-proof and wave-absorbing concrete, which comprises, by mass ratio, 250 to 350 parts of cement, 85 to 95 parts of low-magnetic fly ash, 55 to 65 parts of mineral powder, 800 to 850 parts of wave-absorbing functional aggregate, 1200 to 1400 parts of magnetite sand, 40 to 65 parts of steel fiber, 0.09 to 0.4 parts of graphene oxide, 5 to 6 parts of water reducer, and 175 to 185 parts of water, wherein the low-magnetic fly ash and the wave-absorbing functional aggregate are prepared by the above-mentioned method for preparing the wave-absorbing functional aggregate.

[0020] Furthermore, the particle size of magnetite sand is 315 μm to 2.50 mm, and the apparent density is 4870 kg / m 3 .

[0021] Furthermore, the thermal conductivity of graphene oxide is 5300 W / (m·K) and the density is 2 g / cm 3 .

[0022] Furthermore, the steel fiber is hook-shaped, with a length of 14 mm, a diameter of 0.22 mm, an aspect ratio of 65, and a density of 7850 kg / m 3 , tensile strength is greater than 2000MPa.

[0023] Furthermore, the water reducer is a high-performance polycarboxylate water reducer.

[0024] The present invention also provides a method for preparing radiation-proof and wave-absorbing concrete, the method comprising:

[0025] S1. According to the mass fraction ratio, 0.09-0.4 parts of graphene oxide are ultrasonically dispersed in 10-15 parts of water for 30-60 minutes to obtain a graphene oxide dispersion K for standby use:

[0026] S2, take 250-350 parts of cement, 85-95 parts of low magnetic fly ash, 55-65 parts of mineral powder, 800-850 parts of wave absorbing aggregate and 1200-1400 parts of magnetite sand, stir and mix them evenly to obtain dry material I;

[0027] S3, take 5-6 parts of water reducing agent, add it to the remaining water and stir evenly, add it to the dry material I and mix and stir evenly to obtain slurry J;

[0028] S4. Add graphene oxide dispersion K into slurry J and stir evenly, then add 40 to 65 parts of steel fiber into the slurry and stir evenly to obtain radiation-proof and wave-absorbing concrete.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. The radiation-proof and wave-absorbing concrete of the present invention realizes magnetic loss of electromagnetic waves through the coordination of wave-absorbing functional aggregate and cement paste. The combination of magnetite in the wave-absorbing functional aggregate and magnetite sand as fine aggregate realizes electric loss of electromagnetic waves by adding steel fiber to the cement paste. The coordination of magnetic loss and electric loss improves the absorption efficiency and absorption effect of microwaves and improves the wave-absorbing broadband of concrete.

[0031] 2. The graphene oxide in the radiation-proof and wave-absorbing concrete of the present invention has a high thermal conductivity, which can quickly transfer the heat generated by the aggregate to the cement paste, improve the uniformity of the concrete temperature, and prevent the concrete from cracking; in addition, the oxygen-containing functional groups of the graphene oxide can be tightly combined with the cement paste to improve the mechanical properties of the concrete.

[0032] 3. The present invention uses graphene oxide, which has a relatively low aspect ratio, is hydrophilic, and is relatively easy to disperse. The graphene oxide is evenly dispersed in the cement paste by combining ultrasonic dispersion with a dispersant. By strictly controlling the amount of graphene oxide, it is prevented from forming a conductive network due to excessive addition, thereby avoiding reducing the wave absorption and mechanical properties of the concrete. On the one hand, the polycarboxylate water reducer plays the role of a common water reducer, and on the other hand, because it is an anionic surfactant, it can promote the dispersion of graphene oxide.

[0033] 4. The wave-absorbing functional aggregate prepared by the process of reduction-magnetic separation-inert atmosphere sintering in the present invention has high cylinder pressure strength, high magnetite content and good wave-absorbing performance. The fly ash used to prepare the wave-absorbing functional aggregate has a high iron content, mainly in the form of hematite and magnetite. The weakly magnetic hematite is reduced to strongly magnetic magnetite by residual carbon during the roasting process. No additional reducing agent is added. High-iron fly ash is screened out by magnetic separation. The high-iron fly ash will not sinter into hematite and iron element under the protection of inert gas, thereby increasing the magnetite content of the wave-absorbing functional aggregate and improving its wave-absorbing performance.

[0034] In addition, most of the iron oxides are removed from the low-magnetic fly ash, the intermediate product obtained in the preparation process of the wave-absorbing functional aggregate, the iron content is reduced, and the content of active silicon and aluminum substances is increased, thereby increasing the volcanic ash activity of the fly ash, which is beneficial to improving the strength of the concrete.

[0035] 5. In the present invention, by controlling the sintering process, the prepared wave-absorbing functional aggregate has high density and low porosity; by adding high-density magnetite sand as fine aggregate, the density of concrete is increased, and its protection performance against X-rays and gamma rays is improved; the addition of steel fiber can increase the density of concrete due to its high density, and on the other hand, the steel fiber can prevent sinking caused by excessive density of magnetite sand and improve the uniformity of concrete. At the same time, by strictly controlling the dosage of each component and reasonably controlling the density of concrete, a large amount of microwaves can be avoided from being reflected due to excessive density of concrete, thereby avoiding reducing the wave-absorbing effect. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is further described below in conjunction with specific embodiments:

[0037] Example 1

[0038] A method for preparing a wave-absorbing functional aggregate, comprising:

[0039] S1. placing high iron fly ash containing magnetite and hematite in a roasting furnace, and roasting at a roasting temperature of 800° C. for 30 min to obtain roasted fly ash A, wherein the roasted fly ash A contains magnetite;

[0040] The Fe2O3 content of high iron fly ash A is 14%-20%, the SiO2 content is 45%-54%, the Al2O3 content is 25%-30%, the Na2O content is 0.5%-1%, the K2O content is 0.5%-1%, the CaO content is 1%-4%, the MgO content is 0.5%-3%, and the residual carbon content is 4%-6%.

[0041] In this stage, the hematite in the high iron fly ash A undergoes a reduction reaction at high temperature, and the reaction process is as follows:

[0042] 2C+O2=2CO

[0043] 3Fe2O3+CO=2Fe3O4+CO2

[0044] S2. Disperse the calcined fly ash A in water, wherein the mass ratio of the calcined fly ash A to water is 1:9 to 1:4. In the present embodiment, the mass ratio of the calcined fly ash A to water is 1:5, to obtain a calcined fly ash solution B. Separate the magnetic substance in the calcined fly ash solution B, wherein the main component of the magnetic substance is Fe3O4, to obtain wet high magnetic fly ash C and low magnetic fly ash solution D.

[0045] More specifically, the process of separating magnetic substances is as follows:

[0046] Step S21, stirring the roasted fly ash solution B by a magnetic bar with a magnetic induction intensity of 1T, so that the magnetic substance in the roasted fly ash solution B is adsorbed on the surface of the magnetic bar, and the magnetic substance on the surface of the magnetic bar is collected for later use; repeating the above process until the surface of the magnetic bar with a magnetic induction intensity of 1T is no longer adsorbed with magnetic substances;

[0047] Step S22, stirring the roasted fly ash solution B after the treatment in the above step S21 by a magnetic bar with a magnetic induction intensity of 1.2T, so that the magnetic substance in the roasted fly ash solution B is adsorbed on the surface of the magnetic bar with a magnetic induction intensity of 1.2T, collecting the magnetic substance on the surface of the magnetic bar with a magnetic induction intensity of 1.2T for later use, and repeating the operation until the surface of the magnetic bar with a magnetic induction intensity of 1.2T is no longer adsorbed with magnetic substances;

[0048] Step S23, the collected magnetic substances are mixed to obtain wet high magnetic fly ash C, and the roasted fly ash solution B is processed in step S22 to obtain low magnetic fly ash solution D.

[0049] S3, drying the wet high magnetic fly ash C to constant weight to obtain high magnetic fly ash; drying the low magnetic fly ash solution D to constant weight to obtain low magnetic fly ash; during drying, drying in an oven at a drying temperature of 60°C.

[0050] More specifically, the content of Fe2O3 in high magnetic fly ash is 45% to 60%, and the content of Fe2O3 in low magnetic fly ash is 2% to 6%.

[0051] S4. Granulate the high magnetic fly ash to form raw aggregate balls E with wave absorbing function. When granulating, place the high magnetic fly ash on the disc of a disc ball making machine, and rotate the disc horizontally while sprinkling water until the high magnetic fly ash rolls into balls on the disc, and obtain the raw aggregate balls E with wave absorbing function after drying.

[0052] S5. calcining the wave absorbing functional aggregate green ball E under argon protection, including three stages:

[0053] In the first stage, the preheating temperature is 400°C and the preheating time is 30 minutes;

[0054] In the second stage, the calcination temperature was 1200°C and the sintering time was 20 min;

[0055] In the third stage, rapid cooling for 15 minutes, the temperature drops to room temperature, which is usually 20-25°C, to obtain a coarse wave-absorbing functional aggregate F;

[0056] During the above calcination process, argon gas as an inert atmosphere prevents the magnetite in the wave-absorbing functional aggregate green ball E from being reduced or oxidized, so that a large amount of magnetite remains in the aggregate after the calcination is completed.

[0057] S6. Screening the coarse wave-absorbing functional aggregate F to obtain wave-absorbing functional aggregate, the apparent density of which is 2300-2500 kg / m 3 , cylinder pressure strength is 10~12MPa, and particle size is 5~20mm.

[0058] Example 2

[0059] A radiation-proof wave-absorbing concrete comprises, by weight ratio, 300 parts of cement, 90 parts of low-magnetic fly ash, 60 parts of mineral powder, 817 parts of wave-absorbing aggregate, 1290 parts of magnetite sand, 55 parts of steel fiber, 0.2 parts of graphene oxide, 5.4 parts of water-reducing agent, and 180 parts of water; wherein the low-magnetic fly ash and the wave-absorbing aggregate are prepared by the method of the above embodiment 1; the particle size of the magnetite sand is 315 μm to 2.50 mm, and the apparent density is 4870 kg / m 3 ; The thermal conductivity of graphene oxide is 5300W / (m·K) and the density is 2g / cm 3 The steel fiber is hook-shaped, with a length of 14 mm, a diameter of 0.22 mm, an aspect ratio of 65, and a density of 7850 kg / m 3 , tensile strength is greater than 2000MPa; the water reducer is a high-performance polycarboxylate water reducer.

[0060] The preparation process of the above-mentioned radiation-proof and wave-absorbing concrete is as follows:

[0061] S1. Take 0.2 parts of graphene oxide according to the mass ratio and ultrasonically disperse it in 10 parts of water for 30 minutes to obtain a graphene oxide dispersion K for standby use:

[0062] S2, taking 300 parts of cement, 90 parts of low magnetic fly ash, 60 parts of mineral powder, 817 parts of wave absorbing aggregate and 1290 parts of magnetite sand and mixing them evenly under mechanical stirring to obtain dry material I;

[0063] S3, take 5.4 parts of water reducer, add it to the remaining 170 parts of water and stir evenly, then add it to the dry material I and mix and stir evenly to obtain slurry J;

[0064] S4. Add graphene oxide dispersion K into slurry J and stir evenly, then add 55 parts of steel fiber into slurry J and stir evenly to obtain radiation-proof and wave-absorbing concrete.

[0065] The radiation-proof and wave-absorbing concrete obtained from the vegetation in Example 2 was tested for compression resistance, apparent density, gamma-ray attenuation coefficient, and maximum reflectivity at 8 to 18 GHz. The test results are shown in the following table:

[0066]

[0067] It can be concluded from the test results in the above table that the radiation-proof and wave-absorbing concrete prepared in Example 2 has high compressive strength and good mechanical properties; high maximum reflectivity at 8 to 18 GHz and high wave-absorbing efficiency; large apparent density and gamma-ray attenuation coefficient and good radiation-proof performance.

[0068] It should be noted that in this application, the letters in the calcined fly ash A, calcined fly ash solution B, wet high magnetic fly ash C, low magnetic fly ash solution D, absorbing functional aggregate raw balls E, rough absorbing functional aggregate F, dry material I, slurry J and graphene oxide dispersion K have no special limiting meaning and are only used to distinguish substances and materials.

[0069] This embodiment is only a further explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to this embodiment as needed, but as long as it is within the scope of the claims of the present invention, it will be protected by the patent law.

Claims

1. A method for preparing a wave absorbing functional aggregate, characterized in that: include: S1. placing high iron fly ash containing magnetite and hematite in a roasting furnace, and roasting at a roasting temperature of 800° C. for 30 min to obtain roasted fly ash A, wherein the roasted fly ash A contains magnetite; S2, dispersing the calcined fly ash A in water to obtain a calcined fly ash solution B, separating the magnetic substance in the calcined fly ash solution B to obtain wet high magnetic fly ash C and low magnetic fly ash solution D; S3, drying the wet high magnetic fly ash C to constant weight to obtain high magnetic fly ash; drying the low magnetic fly ash solution D to constant weight to obtain low magnetic fly ash; S4, granulating the high magnetic fly ash to form raw aggregate balls E with wave absorbing function; S5, calcining the wave absorbing functional aggregate green ball E in an inert atmosphere, including three stages: In the first stage, the preheating temperature is 400°C and the preheating time is 30 minutes; In the second stage, the calcination temperature was 1200°C and the sintering time was 20 min; In the third stage, rapid cooling for 15 minutes, the temperature drops to room temperature, and a coarse wave-absorbing functional aggregate F is obtained; S6. Screening the coarse wave-absorbing functional aggregate F to obtain wave-absorbing functional aggregate, wherein the apparent density of the wave-absorbing functional aggregate is 2300-2500 kg / m 3 , cylinder pressure strength is 10~12MPa, and particle size is 5~20mm.

2. The method for preparing a wave absorbing functional aggregate according to claim 1, characterized in that: The high iron fly ash has a Fe2O3 content of 14% to 20%, a SiO2 content of 45% to 54%, an Al2O3 content of 25% to 30%, a Na2O content of 0.5% to 1%, a K2O content of 0.5% to 1%, a CaO content of 1% to 4%, a MgO content of 0.5% to 3%, and a residual carbon content of 4% to 6%.

3. The method for preparing a wave absorbing functional aggregate according to claim 1, characterized in that: The mass ratio of the calcined fly ash A to water is 1:9 to 1:

4.

4. The method for preparing a wave absorbing functional aggregate according to claim 1, characterized in that: The content of Fe2O3 in the high magnetic fly ash is 45% to 60%, and the content of Fe2O3 in the low magnetic fly ash is 2% to 6%.

5. A radiation-proof and wave-absorbing concrete, characterized in that: The composition comprises, by weight: 250 to 350 parts of cement, 85 to 95 parts of low magnetic fly ash, 55 to 65 parts of mineral powder, 800 to 850 parts of wave absorbing aggregate, 1200 to 1400 parts of magnetite sand, 40 to 65 parts of steel fiber, 0.09 to 0.4 parts of graphene oxide, 5 to 6 parts of water reducer, and 175 to 185 parts of water. The low magnetic fly ash and wave absorbing aggregate are prepared by the method described in any one of claims 1 to 4.

6. The radiation-proof and wave-absorbing concrete according to claim 5, characterized in that: The particle size of the magnetite sand is 315 μm to 2.50 mm, and the apparent density is 4870 kg / m 3 .

7. The radiation-proof and wave-absorbing concrete according to claim 5, characterized in that: The thermal conductivity of the graphene oxide is 5300 W / (m·K) and the density is 2 g / cm 3 .

8. The radiation-proof and wave-absorbing concrete according to claim 5, characterized in that: The steel fiber is hook-shaped, with a length of 14 mm, a diameter of 0.22 mm, an aspect ratio of 65, and a density of 7850 kg / m 3 , tensile strength is greater than 2000MPa.

9. The radiation-proof and wave-absorbing concrete according to claim 5, characterized in that: The water reducer is a high-performance polycarboxylate water reducer.

10. A method for preparing radiation-proof and wave-absorbing concrete as claimed in claim 5, characterized in that: The method includes: S1. According to the mass fraction ratio, 0.09-0.4 parts of graphene oxide are ultrasonically dispersed in 10-15 parts of water for 30-60 minutes to obtain a graphene oxide dispersion K for standby use: S2, take 250-350 parts of cement, 85-95 parts of low magnetic fly ash, 55-65 parts of mineral powder, 800-850 parts of wave absorbing aggregate and 1200-1400 parts of magnetite sand, stir and mix them evenly to obtain dry material I; S3, take 5-6 parts of water reducing agent, add it to the remaining water and stir evenly, add it to the dry material I and mix and stir evenly to obtain slurry J; S4. Add graphene oxide dispersion K into slurry J and stir evenly, then add 40 to 65 parts of steel fiber into the slurry and stir evenly to obtain radiation-proof and wave-absorbing concrete.

Citation Information

Patent Citations

  • Electromagnetic wave absorption concrete and production method thereof

    CN106278001A